Pure Papillary Serous Tumors of the Endometrium: A Clinicopathological Analysis of 61 Cases From a Single Institution. Issue 8 (1st November 2009) - Benito, Virginia; Lubrano, Amina; Arencibia, Octavio; ÁLvarez, Eva Elisa; LeÓN, Laureano; Medina, Norberto; FalcÓN, Juan Miguel; FalcÓN, Orlando
Abstract : Objective: The aim of this study was to evaluate the clinicopathological data and prognosis factors corresponding to patients with papillary serous carcinoma of the endometrium treated at a single institution. Methods: Medical and anatomopathological records were reviewed in the Department of Gynecological Oncology of the Canarian University Hospital between 1989 and 2006. Only pure cases of papillary serous carcinoma of the endometrium were included. Survival rates were analyzed using the Kaplan-Meier technique. Results: The study included 61 patients. Stages I, II, III, and IV were identified in 32.8%, 19.7%, 31.1%, and 8.2% of patients, respectively. Event-free survival rates after 5 and 10 years were 59% and 40%, respectively, with a median time of 83 months (95% confidence interval, 63-110). Relapse occurred in 40.5% of the patients. Overall survival rates after 5 and 10 years were 37.7% and 29%, respectively, with a median time of 55 months (95% confidence interval, 40-70). A univariate analysis showed that prognosis factors were tumor markers, stage, myometrial infiltration, lymphovascular invasion, and ganglia involvement. A multivariate analysis showed that tumor markers, stage, and myometrial infiltration had an independent influence on overall survival. Conclusions: Papillary serous carcinoma of the endometrium is a very aggressive type of endometrial carcinoma that behaves more similar to ovarian carcinoma than to endometrial carcinoma. Tumor markers at diagnosis, stage, and myometrial infiltration mainly determine prognosis at our institution.